Avaliação dos aspectos hídricos relacionados ao desenvolvimento da cultura da cana-de-açúcar na Bacia São José dos Dourados - Sumai, Junior de Souza [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
In order to diagnose the influence of culture on water resources, this study was developed according to analyzes the change in occupation of the Bacia São José dos Dourados (BSJD), northeast region, the state of São Paulo, Brazil, the study period is from the year 2003 to 2013. The significant increase in the area under cultivation of sugarcane in BSJD motivated the exploitation of the specific growth rates of sugarcane cultivation in each municipality that composes and also to the knowledge of the industrial sector. On the sector of the sugar industry, and explain the process of industrialization, the amount of installed power plants in the study area, the potential for milling of each industrial plant and average water consumption of the sector is also presented. To the knowledge of the sugarcane industry, a study on the current numbers of the sugarcane market (production of sugarcane, ethanol, sugar), the projection of future market was also investigated, the trends for the coming years and the market expectation was conducted internal / external are present in this work. Another important study in this work is the identification of the problems caused by the change of land use, in addition to the different characteristics between cultures, working with the soil also presents different techniques, these changes can damage the quality of the environment causing serious damage. This work aims to present factors and historical growth of sugarcane sector in the bowl of Bacia São José dos Dourados

Com o objetivo de diagnosticar a influência de uma cultura sobre os recursos hídricos, este estudo foi elaborado de acordo com análises na mudança de ocupação da Bacia São José dos Dourados (BSJD), região noroeste, interior do estado de São Paulo, Brasil, o período de estudo é do ano de 2003 à 2013. O aumento significativo da área de cultivo da cana na BSJD motivou a avaliação dos índices de crescimento específico do cultivo da cana de cada município, que a compõe e também uma ampliação do conhecimento a respeito do setor industrial. Sobre o setor da indústria da cana, além de explanar o processo de industrialização, também é apresentada a quantidade de usinas instaladas na área de estudo, o potencial de moagem de cada planta industrial e o consumo de água médio do setor. Para conhecimento do setor da cana, foi realizado um estudo sobre os números atuais do mercado da cana (produção de cana, de etanol, de açúcar).A projeção do mercado futuro também foi pesquisada, as tendências para os próximos anos e a expectativa do mercado interno/externo estão presentes neste trabalho. Outro importante estudo realizado neste trabalho é a identificação dos problemas causados pela mudança de ocupação do solo, além das características diferentes entre as culturas, o trabalho com o solo também apresenta técnicas diferentes, estas mudanças podem causar prejuízos a qualidade do meio provocando sérios danos. Este trabalho tem como principal objetivo apresentar os fatores e o histórico de crescimento do setor da cana-de-açúcar na Bacia São José dos Dourados
Keywords: Cana de açúcar Cultivo; Bacias hidrograficas - São Paulo (Estado); Agua - Uso; Agroindustria canavieira; Cana-de-açúcar - Cultivo